"Huonoin suomalainen makkara on paljon parempaa mitä paras ruotsalainen makkara" : ruotsinsuomalaisen suomalainen ruokaidentiteetti - Helminen, Ilona (Helsingfors universitet, 2014)
The purpose of this master's thesis was to examine the identity of the Swedish Finns from the perspective of food and food culture. The Swedish Finns are the largest minority group in Sweden. During last years it has been noticed that the Finnish language and the culture do not transmit to the new generations as they used to do. The Swedish Finns and their identity is being discussed in the theoretical section as well as the general human cultural background and the ability of an immigrant to adapt to a new culture. Another important research approach is the food culture and the food preferences. The research also discusses the change in the immigrant's food culture when a person moves to a new country and cultural environment. The research was qualitative by nature and the research data was gathered by using an electronic questionnaire. The questionnaire had mainly open-ended questions. A snowball sampling was helpful. The questionnaire was also shared with a closed Swedish Finns' Facebook group with more than 2000 members on it. There were 39 responses from people with a Finnish background who had lived different lengths of time in Sweden. The data was analysed by using a content analysis with themes and classifications. The Swedish Finns are a heterogeneous group. The common factor for the ones taking part in the research was their Finnish background. For the most of them the Finnish roots and food meant memories from childhood. These memories might have been connected with certain kind of food such as rye bread and Karelian pie or smells like the baking day at the grandmother's home. The Swedish Finns felt that seasonal food such as Christmas food and particularly Christmas casseroles were highly important. These memories were significant and they wanted to be passed on to their own children. The ones answering the questionnaires had a lot of knowledge and skill in the Finnish food and the food culture. They also wanted to maintain the Finnish food culture and teach it to their children. Pro gradu ...